O fascínio do serial killer: protagonismo e naturalização da anormalidade em Dexter - Santos, Thiara Ribeiro (2017)
This research investigates the narratives of television series about serial killers, focusing most attention on the North American show Dexter, broadcast from 2006 to 2013, while at the same time comparing the context of the series to others of the same genre. In order to learn how the fascination of crime is narrativized in this type of program, our aim was to identify the similarities and differences, compare the narratives, and the main conflicts of each series, the protagonism of the serial killer, the relations between the subject-characters and complex issues related to actions and characteristics of each serial killer and the development of the narrative itself – all focused on the protagonist’s compulsion to kill, while taking into consideration their permanent invisibility and the social ties between them and the other characters; thus we look back in time to delve into the discursive processes of old movies with the same theme in order to understand how the world of series was established. We start with the assumption that a transformation has been made to the narrative structure and character of the serial killers in audiovisual productions over recent decades. Under this context, there is a need to understand how audiovisual languages are used within series, how they intensify normal versus abnormal opposition, how the viewers’ complicity is summoned, and how violence and perversion become elements of the social structure and eventually even agents of the actions. In our view, questioning what retains the tension in the narrative of the Serial Killers TV series is one way of assessing our processes of true meaning and civil morality. This theory is based on knowledge of the areas of Audiovisual, Semiotics, Psychoanalysis, Sociology and Philosophy. For the audiovisual area, we benefitted from input from Neale, Arlindo Machado and Sonia Rodrigues who have studied narrative strategies in dramatic series; the studies relating to cinema were enhanced by contributions from Shaviro and Naremore and the studies of series consolidated by Douglas L. Howard; investigations made about cinema and representation by Ismail Xavier also strengthened the analyses of this thesis. The analysis of the generative route toward the meaning of narratives was bolstered by the discursive-semiotic contributions from Eric Landowski and Ana Claudia de Oliveira, and the tensive-semiotics contributions from Claude Zilberberg. With regard to psychoanalysis, particularly to focus on the Lacanian concept of perversion and neurosis, we use texts by Nasio, Žižek, Bond, Philippe Julien and Antonio Quinet, which assist us in explaining the universe of our subject, the serial killer. For the sociological and ethical discussions about abnormality and perversity we adopt the thoughts of Dany-Robert Dufour and Simpson